Work absenteeism across economic activity sectors and its association with COVID-19-like illness prevalence in the Netherlands, 2020–2023 - Hester Korthals Altes; Jan Van De Kassteele; Bram Wisse; Maria Xiridou; Albert Jan Van Hoek; Jacco Wallinga (Epidemics, 2025)
The monitoring of work absenteeism can inform pandemic decision making, besides the surveillance of disease end-points like mortality and intensive care bed occupancy. For instance, high disease prevalence accompanied by elevated levels of absenteeism in the healthcare sector will increase the strain on the health care system, and may necessitate adaptation of the control measures. This highlights the need to assess the association between COVID-19 disease prevalence and absenteeism in relevant economic sectors. We initiated the comprehensive monitoring and analysis of work absenteeism and developed an autoregressive time series model which combined COVID-19 prevalence as measured through syndromic surveillance, with absenteeism across various economic activity sectors in the Netherlands. The analysis was updated regularly and shared with policy makers. Overall, prevalence of COVID-19-like illnesses was the most important contributor to variation in absenteeism over the period November 2020-May 2023, with absenteeism rates varying markedly between activity sectors. Of the sectors well-covered by the absenteeism database, the Education and Logistics sectors showed the greatest contribution of a seasonal pattern independent of COVID-19 to absenteeism.